Three pillars of skepticism in classical India Nagarjuna, Jayarasi, and Sri Harsa - Mills, Ethan (Studies in comparative philosophy and religion., 2018)
This book argues that the philosophical history of India contains a tradition of skepticism about philosophy represented most clearly by three figures: Nāgārjuna, Jayarāśi, and Śrī Harṣa. Furthermore, understanding this tradition ought to be an important part of our contemporary metaphilosophical reflections on the purposes and limits of philosophy.